Enhancing the energy and exergy performance of a photovoltaic thermal system with ∇-shape collector using porous metal foam. (25th September 2022) - Mustafa, Jawed; Alqaed, Saeed; Sharifpur, Mohsen
Abstract: The use of porous media in heat transfer systems leads to a rise in the heat transfer surface area and pressure loss of the working fluid, the first of which is desirable and the second is undesirable. The effect of porous metal foam positioning on the energy and exergy performances of an air-based photovoltaic thermal system with ∇ -shape collector is investigated in this research. For this purpose, porous foam is placed once in the channel between the photovoltaic panel and the collector (system II), again in the channel between the collector and the back insulation wall (system III), and finally in both channels (system IV). The results are compared with each other and with those of the system without porous metal foam (system I). The energy balance equation is written for each part of the system, and the resulting system of equations is solved with a code written in MATLAB. The mathematical modeling was performed for several values of air mass flow rate. The results showed that the maximum overall energy efficiency (61.53–111.49%) and overall exergy efficiency (14.18–17.46%) belong to systems II and IV.